2009
DOI: 10.1371/journal.pone.0005873
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Validation of FePro Cell Labeling Method

Abstract: Current method to magnetically label cells using ferumoxides (Fe)-protamine (Pro) sulfate (FePro) is based on generating FePro complexes in a serum free media that are then incubated overnight with cells for the efficient labeling. However, this labeling technique requires long (>12–16 hours) incubation time and uses relatively high dose of Pro (5–6 µg/ml) that makes large extracellular FePro complexes. These complexes can be difficult to clean with simple cell washes and may create low signal intensity on T2*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 19 publications
8
77
0
Order By: Relevance
“…Various modifications of labeling protocols using ferumoxides have been reported in order to decrease the occurrence of extracellular iron deposits, like the use of heparin washes, additional incubation time or a different timing of complex formation (7,12,13,16). We did not include these adjustments in our main experiments, in order to better compare both techniques.…”
Section: Transfection Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…Various modifications of labeling protocols using ferumoxides have been reported in order to decrease the occurrence of extracellular iron deposits, like the use of heparin washes, additional incubation time or a different timing of complex formation (7,12,13,16). We did not include these adjustments in our main experiments, in order to better compare both techniques.…”
Section: Transfection Agentmentioning
confidence: 99%
“…Full Paper approximately 100% have been reported regarding human bone marrow stromal cell (hBMSC) labeling, both methods are hampered by the occurrence of extracellular iron nanoparticle aggregates (5,7,(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…13 We have effectively assembled different elements (PEG and mAb) into a magnetic nanoparticle (SPION) without altering their inherent properties and engineered a SPION-based nanoprobe through an electrostatic interaction. This nanoprobe is capable of selectively separating progenitor cells from a heterogeneous population of cells and subsequently enables the cells to be tracked through noninvasive molecular imaging.…”
Section: Discussionmentioning
confidence: 99%
“…21 We evaluated the rate of clearance of iron from labeled cells with concomitant assessment of their viability in long-term culture. Quantitative analysis of the iron content of the labeled cells, using a standard protocol by Janic et al 13 showed a gradual and steady decrease in iron concentration over time, suggesting possible clearance of iron by endogenous pathways. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation